2020
DOI: 10.33323/indigenous.v2i2.38
|View full text |Cite
|
Sign up to set email alerts
|

Uji Kualitas Air Pada Sumber Mata Air Waipadda Desa Anajiaka Kecamatan Umbu Ratu Nggay Barat Kabupaten Sumba Tengah

Abstract: Abstrak Air merupakan bahan yang sangat vital yang tidak terpisahkan dari kehidupan mahkluk hidup di muka bumi ini.Segi kualitas, beberapa persyaratan yang harus dipenuhi sebagai air bersih yaitu parameter fisik ,kimia dan biologi.Salah satu mata air yang penggunaannya sangat vital bagi masyarakat Sumba Tengah adalah mata air Waipadda. Tujuan dari penelitian iniuntuk mengujikualitas mata air Waipada di desa Anajiaka kecamatan Umbu Ratu Nggay Barat kabupaten Sumba Tengah dengan berdasarkan parameter fisik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The value of the degree of acidity (pH) expresses the intensity of acidity or alkalinity of a liquid dilute and represents the concentration of the hydrogen ion. If the pH is less than 6.5 or greater than 9.2, it will corrode the water pipes and can convert some chemical compounds into toxins that are harmful to the health of humans (Marak et al, 2019). The low pH value of the Cikrebek spring is suspected of having Apu plants, while in Sirah Citanggulun, there are activities for bathing and washing.…”
Section: Chemical Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…The value of the degree of acidity (pH) expresses the intensity of acidity or alkalinity of a liquid dilute and represents the concentration of the hydrogen ion. If the pH is less than 6.5 or greater than 9.2, it will corrode the water pipes and can convert some chemical compounds into toxins that are harmful to the health of humans (Marak et al, 2019). The low pH value of the Cikrebek spring is suspected of having Apu plants, while in Sirah Citanggulun, there are activities for bathing and washing.…”
Section: Chemical Parametermentioning
confidence: 99%
“…Regarding the previous studies, spring water is a polluted contaminant with chemical, physical, and biological exceed a standardized. Previous research on spring water and its quality has been carried out by Marak et al (2019) in Waipadda Spring, Sumba Tengah Regency. The research found that water quality at the Waipadda Spring, compared to Class I PP No.…”
Section: Introductionmentioning
confidence: 99%